Abdominal Compartment Syndrome after Cesarean Section: A Case Report - Nazanin Beheshtian; Samaneh Akbarzadeh; Bita Zargaran; Helena Azimi; Amir Hossain Jafarian; Zohreh Yousefi; Akram Khalaati (Mashhad University of Medical Sciences, 2020)
Background: Abdominal compartment syndrome (ACS) after cesarean section (CS) is a rare event which is associated with an increased risk of morbidity and mortality. This complication may arise as a result of musculoskeletal trauma and fluid accumulation. The present report aimed to introduce a case of ACS after the cesarean section. Case report: We present the case of a 32-year old woman who developed abdominal compartment syndrome 4 days after the cesarean section. The patient's symptoms included severe abdominal distension, fever, decreased haemoglobin level despite normal blood pressure, and decreased urine output. Nasogastric/colonic decompression was not effective. Computed tomography (CT) scan demonstrated partial bowel obstruction. After an emergency decompressive laparotomy due to increased intra-abdominal pressure, the patient was diagnosed with ACS and rescued by supportive conservative treatment. Conclusion: ACS is a rare complication of CS; nonetheless, delayed diagnosis and intervention can cause irreversible damages. The physicians and midwives should be cautious about post caesarean signs and symptoms, including massive abdominal distention, pain, fever, difficulty breathing, and decreased urine output. Conservative therapeutic strategy and decompressive laparotomy is the gold standard treatment for this disease.